Troubling the Blurred Boundaries of Online Professionalism - MacLean, Sara B (Proceedings of the International Conference on Networked Learning, 2016)
Recently, professional associations have issued new guidelines that apprehensively embrace the use of social media encouraging their members to use the medium ‘appropriately’. In the academic literature, a discussion has been taking place around ‘online professionalism’ or ‘e-professionalism’ with some in professional education beginning to ponder about how to facilitate the development of this extended form of professionalism. Within both of these discourses, the trope of boundary blurring is often invoked as an indication of the challenging potentials of social media to the professions and professional education. However, little regard is given to what these boundaries are and how they are formed. In this short paper reporting on research in progress, I seek not to blur the boundaries but to trouble them - to bring them more in focus and to treat them as an assemblage through an ANT analysis for the purpose of informing how we educate for professionalism. Theoretical approach: Employing an Actor Network Theory sensibility, this research reconceptualises boundaries as networks - heterogeneous assemblage of bodies, devices, technologies, algorithms, standards, representations etc. Thus, materials move from factors in boundary practices to actors constructing the boundaries in a process of generative materiality. As they are networks, boundaries are being made and re-made as the relations are constantly being performed (Latour, 2005). Moreover, networks are not inherently consistent. Parts of the network may be in conflict creating fissures and tensions. Applying this to boundaries, therefore, would allow for an analysis that explores, as Law (1992) has put it, "the precarious mechanics of organisation" (p. 389). It will inquire about what is invited and what is excluded in the boundary practices of online professionalism as well as tracing specific ways things are enacted - what enables or constrains these enactments. It will also explore what effects these assemblages produce. Methodology: The research will focus on two groups of pre-professional students in their final year of education, one from social work and the other from nursing. It will follow a three stage design. The initial stage is an individual interview where vignettes are employed to stimulate reflection on online professionalism and to draw out the boundaries of concern. The second stage is a group interview where participants discuss digital artefacts that may surprise or push boundaries. The last stage involves individual participants tracing their digital footprint with the research investigating the materialities that assemble into their notion of online professionalism.